PERAN LAYANAN KONSELING INDIVIDU DENGAN TEKNIK SOSIAL SKILL TRAINING UNTUK MENGURANGI PERILAKU WITHDRAWAL PADA SISWA KELAS X7 SMA NEGERI 1 COLOMADU TAHUN PELAJARAN 2025/2026 - Ariati Dewi, Sheilla; Adi Putro, Eko; Dwi Sholikhah, Linda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to determine the role of individual counseling services with social skill training techniques in reducing withdrawal behavior in class X7 students of SMA Negeri 1 Colomadu in the academic year 2025/2026. This research was conducted at SMA Negeri 1 Colomadu. The subject of this study was 1 student from class X7. The research method used was descriptive qualitative research. Data collection techniques used were interviews, observation, and documentation. The validity of the data was ensured using technical triangulation and time triangulation. The data analysis technique used followed the Miles and Huberman model, which includes the stages of data collection, data reduction, data presentation, and drawing conclusions. According to the results of the research conducted, the social skill training technique helped students acquire direct learning on how to build social interactions with peers. Based on the research results regarding the role of individual counseling services with social skill training techniques to reduce withdrawal behavior in class X7 students of SMA Negeri 1 Colomadu in the academic year 2025/2026, it can be concluded that individual counseling services with social skill training techniques can help in reducing withdrawal behavior in students.